2018
DOI: 10.1097/j.pain.0000000000001391
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain and pain interference are linked to alpha-band slowing and reduced beta-band magnetoencephalography activity within the dynamic pain connectome in patients with multiple sclerosis

Abstract: Chronic pain is a common occurrence in multiple sclerosis (MS) that severely affects quality of life, but the underlying brain mechanisms related to these symptoms are unknown. Previous electroencephalography studies have demonstrated a role of alpha-band and beta-band power in pain processing. However, how and where these brain signals change in MS-related chronic pain is unknown. Here, we used resting state magnetoencephalography to examine regional spectral power in the dynamic pain connectome-including are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 82 publications
3
65
1
Order By: Relevance
“…This hypothesis was further supported by the positive correlation between resting-state alpha oscillation power and somatization severity across the SPD patients, where somatization severity and somatosensory amplification are closely linked [53, 54]. Although the observed increased alpha oscillation among SPD patients was consistent with findings from many chronic pain studies [17, 19, 43, 55], it was in contrast with experimental pain studies [12, 13, 56] showing the negative correlation between prestimulus alpha oscillation and subsequent pain perception. This could be arising from the differences between experimental pain (well controlled with limited duration and specified location) and clinical pain (long lasting and widespread, with pain interference such as sleep interference), particularly considering the absence of organic pathology involved in the maintenance of chronic pain suffered by SPD patients.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This hypothesis was further supported by the positive correlation between resting-state alpha oscillation power and somatization severity across the SPD patients, where somatization severity and somatosensory amplification are closely linked [53, 54]. Although the observed increased alpha oscillation among SPD patients was consistent with findings from many chronic pain studies [17, 19, 43, 55], it was in contrast with experimental pain studies [12, 13, 56] showing the negative correlation between prestimulus alpha oscillation and subsequent pain perception. This could be arising from the differences between experimental pain (well controlled with limited duration and specified location) and clinical pain (long lasting and widespread, with pain interference such as sleep interference), particularly considering the absence of organic pathology involved in the maintenance of chronic pain suffered by SPD patients.…”
Section: Discussionsupporting
confidence: 71%
“…An increase of the oscillation at alpha band frequency has ever been reported in chronic pain patients [17, 43]. For example, among patients with multiple sclerosis, Kim et al observed an increase of alpha oscillation power within several nodes of the salience network and ascending nociceptive pathway [17], which was interpreted as a result of overflowing sensory information due to a reduced sensory gating. The increased alpha oscillation has also been identified among migraine patients, suggesting an overintegration of sensory information in these patients [48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept has been developed in other fields such as cognition and aging, 17 and we have discussed this in relation to acute 34 and chronic pain. 4,23,35…”
Section: How Are Pain States and Pain Trait Represented In The Brain?mentioning
confidence: 99%